Identification and characterization of a heterotrimeric archaeal DNA polymerase holoenzyme - Jiangyu Yan (Nature Portfolio, 2017)
The current model for B-family DNA polymerases in archaea is one of single-subunit enzymes in contrast to the multi-subunit complexes in eukaryotes. Here the authors show that PolB1 fromSulfolobus solfataricusexists as a heterotrimeric complex in cell extracts.